2016
DOI: 10.1093/pm/pnw161
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Initiatives to Overcome Language Barriers and Improve Attendance: A Cross-Sectional Analysis of Adherence in an Inner City Chronic Pain Clinic

Abstract: The results of this retrospective cross-sectional analysis of patients’ adherence with scheduled appointments in an inner-city chronic pain clinic suggests that targeted initiatives including a pre-clinic reminder phone call in the patient’s own language may help to overcome language barriers and improve access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The aforementioned associations hold in subgroup analyses, which lend additional credence to our concept that the important component of the intervention is the attunement, which is in line with the importance of cultural and language concordance for patient-provider interactions, especially in the Hispanic immigrant populations[1,2,7,23]. We note that Spanish was only used in about 29 percent of the calls made.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The aforementioned associations hold in subgroup analyses, which lend additional credence to our concept that the important component of the intervention is the attunement, which is in line with the importance of cultural and language concordance for patient-provider interactions, especially in the Hispanic immigrant populations[1,2,7,23]. We note that Spanish was only used in about 29 percent of the calls made.…”
Section: Resultssupporting
confidence: 75%
“…We hypothesized that patient concerns about cultural incongruence may be ameliorated by human outreach in the patient’s preferred language[1,7]. Based on retrospective cohort studies, we demonstrated that targeted health system improvements can improve access[2]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations